Vegetables, an innovative nut: a marketing plan developed for PepsiCo Iberia - Braga, Manuel Maria Godinho Vieira dos Reis (2017)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics